Bromohydrin pyrophosphate enhances antibody-dependent cell-mediated cytotoxicity induced by therapeutic antibodies - Gertner-Dardenne, Julie; Bonnafous, Cecile; Bezombes, Christine; Capietto, Aude-Hélène; Scaglione, Virginie; Ingoure, Sophie; Cendron, Delphine; Gross, Emilie; Lepage, Jean-François; Quillet-Mary, Anne; Ysebaert, Loîc; Laurent, Guy; et al. (Blood, 2009)
In human blood, 1% to 5% of lymphocytes are γδ T cells; they mostly express the γδ T-cell receptor (TCR)Vγ9, recognize nonpeptide phosphoantigens (PAgs) produced by microbes and tumor cells, and mediate different modes of lytic activities directed against tumor target cells. Antibody-dependent cell-mediated cytotoxicity (ADCC) mediated by cytolytic lymphoid cells is essential for the clinical activity of anticancer monoclonal antibodies (mAbs), but whether PAgs affect ADCC by γδ T cells is unknown. Here we report that, in association with the CD20+-specific mAb rituximab (RTX), the synthetic PAg bromohydrin pyrophosphate (BrHPP) increased TCRVγ9+ cell binding to CD20+ lymphoma cells in vitro. This combination activated phospho-ZAP70 and phospho-ERK1/2 signaling in TCRVγ9+ cells and strongly enhanced their ADCC activity. We obtained similar results with BrHPP in the context of the mAbs alemtuzumab and trastuzumab. Furthermore, BrHPP enhanced RTX-mediated depletion of CD20+ cells in vitro from peripheral blood mononuclear cells of healthy subjects and enhanced ADCC by γδ T cells from patients with chronic lymphocytic leukemia. In cynomolgus macaques, a regimen combining RTX, BrHPP, and IL2 activated TCRVγ9+ lymphocytes and enhanced B-cell depletion from blood and lymph nodes. Thus, the combination with BrHPP PAg is able to improve the efficacy of cancer immunotherapy by therapeutic mAbs.